Effects of soil fluoride pollution on wheat growth and biomass production, leaf injury index, powdery mildew infestation and trace metal uptake. (1st April 2022) - Ahmad, Muhammad Nauman; Zia, Afia; van den Berg, Leon; Ahmad, Yaseen; Mahmood, Rashid; Dawar, Khadim Muhammad; Alam, Syed Sartaj; Riaz, Muhammad; Ashmore, Mike
Abstract: Fluoride (F) is an emerging pollutant that originates from multiple sources and adversely affects plant growth and nutrient bioavailability in soil. This greenhouse study investigated the effects of soil F (0, 10, 20, 50, 100, 200 mg kg −1 ) on morpho-physiological growth characteristics of wheat, soil F contents, and bioavailability and uptake of F, phosphorus (P), sulphur (S), potassium (K), calcium (Ca), magnesium (Mg), aluminium (Al), iron (Fe), manganese (Mn), silicon (Si) and zinc (Zn) by wheat. Higher F significantly reduced plant height and number of leaves particularly at early growth stages and increased visible leaf injury index. Powdery mildew infestation coincided with leafy injury and was higher in elevated soil F treatments. Fluoride treatments (>50 mg kg −1 ) significantly increased water (H2 O)- and calcium chloride (CaCl2 )-extractable F contents in soil. Water-extractable soil F contents from soil in all concentration were higher than CaCl2 -extractable F. This increased F bioavailability resulted in significantly higher F uptake and accumulation in live leaves, dead leaves and grains of wheat which followed order: live leaves > dead leaves > grains. Leaf injury index and number of dead leaves correlated significantly positively with soil H2 O- and CaCl2 -extractable F contents. Patterns of nutrient (P, K, S) and trace metals (Al, Ca, Mg, Fe, Mn, Si, Zn) varied significantly with F concentrations and between live and dead leaves, and grains except for Zn. Dead leaves generally had higher nutrients and trace metals than live leaves and grains. Fluoride contents in live leaves, dead leaves and grains showed positive correlations with nutrient elements but negative with trace metals. Number of dead leaves correlated negatively with Al, Ca, Fe, Mg, S and Si but positively with P and Zn contents in dead leaves whereas leaf injury index showed positive correlation with Fe, K, P, Si, Zn, S but negative with Al, Ca and Mg contents. These observations provided evidence of higher F uptake and associated impairment in nutrient and trace metal accumulation which caused leaf injury accompanied by powdery mildew infestation in wheat. However, further research in the region is required to confirm the relationship between F pollution, leaf injury and trace metal accumulation in crops under field conditions. Graphical abstract: Image 1 Highlights: Effects of soil F (0, 10, 20, 50, 100, 200 mg kg −1 ) were investigated on wheat. Fluoride reduced plant height, number of leaves and biomass. Fluoride in live and dead leaves correlated positively with soil F. Leaf injury index and dead leaves correlated positively with soil F. Trace metal and F accumulation encouraged powdery mildew infestation.